2020
DOI: 10.1021/acsnano.0c08356
|View full text |Cite
|
Sign up to set email alerts
|

Toward Informed Design of Nanomaterials: A Mechanistic Analysis of Structure–Property–Function Relationships for Faceted Nanoscale Metal Oxides

Abstract: Nanoscale metal oxides (NMOs) have found wide-scale applicability in a variety of environmental fields, particularly catalysis, gas sensing, and sorption. Facet engineering, or controlled exposure of a particular crystal plane, has been established as an advantageous approach to enabling enhanced functionality of NMOs. However, the underlying mechanisms that give rise to this improved performance are often not systematically examined, leading to an insufficient understanding of NMO facet reactivity. This criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 281 publications
0
33
0
Order By: Relevance
“…To further reveal the dominant exposed facets of the prepared In 2 O 3 , HRTEM, and SAED were used to characterize the microstructure of In 2 O 3 . The lattice fringes and diffraction spots indicated that the dominant exposed facets of In 2 O 3 –P are {111} Ia 3̅ and {110} Ia 3̅ (Figure b), , while {012} R 3̅ c , and {110} R 3̅ c are the dominant facets in In 2 O 3 -L (Figure f), and {110} R 3̅ c is the major facet in In 2 O 3 -R (Figure j). Thus, the distinct morphologies and facet-exposures of the prepared In 2 O 3 could be summarized as In 2 O 3 –P presents in a crystal shape of a hexahedral plate with {111} Ia 3̅ and {110} Ia 3̅ facets exposure (Figure d), In 2 O 3 -L exhibits a flat hexagonal prism shape (further-developed In 2 O 3 laminas) with {110} R 3̅ c and {012} R 3̅ c facets exposure (Figure h), and In 2 O 3 -R grown as an oblique four-prism with {110} R 3̅ c facet as the only exposed facet (Figure l).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further reveal the dominant exposed facets of the prepared In 2 O 3 , HRTEM, and SAED were used to characterize the microstructure of In 2 O 3 . The lattice fringes and diffraction spots indicated that the dominant exposed facets of In 2 O 3 –P are {111} Ia 3̅ and {110} Ia 3̅ (Figure b), , while {012} R 3̅ c , and {110} R 3̅ c are the dominant facets in In 2 O 3 -L (Figure f), and {110} R 3̅ c is the major facet in In 2 O 3 -R (Figure j). Thus, the distinct morphologies and facet-exposures of the prepared In 2 O 3 could be summarized as In 2 O 3 –P presents in a crystal shape of a hexahedral plate with {111} Ia 3̅ and {110} Ia 3̅ facets exposure (Figure d), In 2 O 3 -L exhibits a flat hexagonal prism shape (further-developed In 2 O 3 laminas) with {110} R 3̅ c and {012} R 3̅ c facets exposure (Figure h), and In 2 O 3 -R grown as an oblique four-prism with {110} R 3̅ c facet as the only exposed facet (Figure l).…”
Section: Resultsmentioning
confidence: 99%
“…Rather than introducing foreign components, facet engineering could provide a simpler but effective approach to fine-tune the photocatalysts’ physicochemical properties. Recently, facet engineering techniques have been applied in developing effective catalysts for pollution control and energy conversion . For instance, the photocatalytic degradation performance of methyl orange (MO) was distinct among the various facets of TiO 2 (e.g., {001}, {010}, and {101}), while {001} facets exhibited 1.79 and 3.22 times higher kinetic rate than that of the {010} and {101} facets, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of Cu/CeO 2 catalysts in the CO oxidation reaction is dependent on the exposed facet of CeO 2 , [ 8 ] and the synergy between Cu and CeO 2 phases, which is related to the interfacial reactivity, presence of O vacancies, enhanced reducibility of CeO 2 , and easy interplay between interfacial redox pairs (Cu +2 /Cu +1 and Ce +4 /Ce +3 ). [ 9 ] Furthermore, the size, shape, and electronic state of Cu/CeO 2 nanoparticles allow modulating the SMSI effect that, in turn, influences on the reactivity in the CO oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, however, a critical question arises: Is it feasible to adjust the surface chemistry of earth-abundant but relatively inactive materials in order to exhibit similar or ever superior performance to that of NMs? On account to the enormous progress so far accomplished on nano-synthesis, surface/interface functionalization and catalyst promotion fields, the answer to this question is definitely yes, as recently demonstrated [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…High intrinsic activity of interfacial sites However, it is well-known today-thanks to the huge progress in cutting-edge characterization techniques-that the individual characteristics of catalyst's counterparts can notably affect not only their own activity but also the interaction between them with great consequences in catalysis. More specifically, by adjusting the geometrical and electronic features of the different counterparts through suitable synthetic and promotional routes highly active materials are obtained [12][13][14][15][16][17][18][19]21,22,24,27,56,[62][63][64][65][66][67][68][69][70][71][72][73][74]. Table 1 depicts at a glance, the main physicochemical modifications that can be induced by adjusting each of the aforementioned parameters.…”
Section: Introductionmentioning
confidence: 99%